Food acceptance and neophobia in children with phenylketonuria: a prospective controlled study. Issue 4 (29th October 2015) - Evans, S.; Daly, A.; Chahal, S.; MacDonald, J.; MacDonald, A.
Abstract: Background: In phenylketonuria (PKU), little is known about the effect of bitter‐tasting phenylalanine‐freel ‐amino acid exposure on taste preference development. The present prospective study aimed to determine the flavour preferences of children with PKU versus healthy control children. Methods: Thirty‐five children with PKU and 35 age/gender‐matched controls, aged 4–13 years, tasted 10 blinded puree foods in random order. They were rated using a seven‐point pictorial hedonic scale (super yummy to super yucky) and ranked in preferential order. Caregivers completed a neophobia and food frequency questionnaire on behalf of their children. Results: Both PKU and control groups rated sweet foods higher than savoury, bitter and sour foods. However, control children ranked fruits as a group higher than PKU children (mean 3.7 versus 4.6; P  = 0.03), whereas PKU children ranked vegetables as a group higher than controls (mean 5.6 versus 6.3; P  = 0.05). Children with PKU had more neophobia and were untrusting/fearful of new foods. Conclusions: Although there was some evidence to suggest that children with PKU aged ≥4 years prefer savoury foods (vegetables) more than control children, they did not prefer bitter‐tasting foods, and so early and persistent administration of bitter‐tastingl ‐amino acids was not associated with apparent taste imprinting. Neophobia appears to play significant part in food refusal in PKU, perhaps more so than taste preferences.